RAINFORESTATION IMPLEMENTATION AND DURKHEIM’S NOTION OF MECHANICAL SOLIDARITY: FROM THE EXPERIENCES OF THE PIONEERING ADOPTERS OF THE CIENDA SAN VICENTE FARMERS ASSOCIATION IN BAYBAY CITY, LEYTE - Fernandez, Guiraldo C.; Bande, Marlito Jose M. (Journal of Agriculture and Technology Management; Vol 21 No 1 (2018): Journal of Agriculture and Technology Management (JATM) Volume 21 January - June 2018 Issue, 2018)
Rainforestation is a technology designed to make use of unproductive lands by planting native tree species which are not widely used in the Philippine government’s reforestation program. In ensuring that rainforestation would be effectively implemented, the Visayas State University (VSU) with the help of the German Cooperation Agency (GIZ) has entered into a partnership with the Cienda San Vicente Farmers’ Association (CSVFA) in Baybay City, Leyte. More than twenty years after implementation, the CSVFA rainforestation farm is presently standing in Barangay Gabas, Baybay City, Leyte. It is in this aspect that this study would investigate whether or not Durkheim’s notion of mechanical solidarity had served as a factor for the success of the existing demonstration farm especially in its implementation stage. Using the method of interpretative textual analysis and key informant interviews through hermeneutic phenomenology, this study concludes that 1) the achievement of the pioneering rainforestation adopters is inspired by their collective drive to protect of what is left of the natural environment; 2) this study also concludes that the success of CSVFA rainforestation efforts is also attributable to the nature of their society which is somewhat pre-industrialized and small – a clear manifestation of Durkheim’s mechanical solidarity, and lastly; 3) this study also concludes that the very notion that there is no personal property in relation to their notion of ownership to the rainforestation demonstration farm and that there is only the existence of collective property drives people to care for it and work for the sake of its well-being. With this, this paper has arrived at a general conclusion that Durkheim’s notion of mechanical solidarity is construed to be one of the significant factors in the implementation and success of the CSVFA rainforestation farm.